A Survey on Wireless Network Intrusion Detection - Maheswari, S.; Pamila, J. C. Miraclin Joyce (IRO Journal on Sustainable Wireless Systems, 2022)
Artificial Intelligence (AI) discoveries have intensified in recent years as a result of the industry’s widespread adoption of this technology. The important field of AI is neural networks, that allow commercial usage of capabilities that were previously unattainable through computer use. One of the domains in which neural network is widely studied for increasing general security and data privacy is IDS. Using various machine learning approaches, this article provides a complete review of recent research on neural network topologies and types of intrusion detection systems.